Spin-polarized alternating-current electroluminescent device, light-emitting panel and application

By introducing spin polarization layer and coplanar electrode structure of chiral materials into spin polarization alternating electroluminescent devices, the existing spin-LED devices have solved the low spin polarization rate and the inability to control different spin polarizations simultaneously. The problem of directional light realizes efficient spin polarized light production and multi-directional light control.

CN119451402APending Publication Date: 2025-02-14SHENZHEN MSU-BIT UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568093.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing spin-LED devices have low spin polarization rates, and cannot control and generate light in different spin polarization directions at the same time, limiting their application scenarios.

Method used

By introducing a spin polarization layer of chiral materials into spin-polarized alternating electroluminescent devices, the alternating current driving mechanism is used to improve the spin polarization rate, and different spin polarization directions in the same plane are achieved through the coplanar electrode structure Light control.

Benefits of technology

It realizes efficient production of spin-polarized light and simultaneously controls and generates light in different spin polarization directions in the same plane, breaking through the limitation that spin-LED can only produce single spin polarized light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451402A_ABST
    Figure CN119451402A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectricity, and discloses a spin polarization alternating current electroluminescent device which comprises a substrate 1, a lower electrode layer 2, a lower dielectric layer 3, a hole injection layer 4, a hole transport layer 5, a luminescent layer 6, an electron transport layer 7, an electron injection layer 8, an upper dielectric layer 3, an upper electrode layer 2 and a protective layer 9 from bottom to top. The spin polarization layer 11 is used for simultaneously controlling and generating light in different spin polarization directions in the same plane and changing the luminous intensity by adjusting the driving voltage or frequency, and the spin polarization layer 11 is positioned between the hole transport layer 5 and the luminous layer 6 or between the luminous layer 6 and the electron transport layer 7; the spin polarization layer 11 is made of a chiral material. According to the spin-polarized light source, spin-polarized light can be efficiently generated, and the problem that in the prior art, spin-polarized light of a spin-LED is low in spin polarizability is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optoelectronic technology, and in particular to a spin-polarized alternating current electroluminescent device, a light-emitting panel and applications. Background Art

[0002] Chiral materials and their mirror images are called enantiomers because they have an intrinsic inversion symmetric structure. These materials exhibit rich physical properties, such as circular dichroism, circularly polarized fluorescence, nonlinear optical effects, etc. At present, chiral optoelectronic devices are mainly completed with the help of optical auxiliary components such as polarizers and quarter glass slides. This method is inefficient, costly and complex in structure. New materials with chiral optical properties can reduce the use of these optical devices, reduce space occupation and simplify the device structure. For example, by combining chiral organic materials with luminescent materials, spin-polarized light-emitting diodes (spin-LEDs) have been realized experimentally, while overcoming the disadvantage that traditional optoelectronic materials require external electric and magnetic fields to control spin and charge. In traditional spin-LED devices, by introducing chirality into the luminescent material or charge transport layer, a series of luminescent materials (perovskites / quantum dots / organic luminescent materials) or spin charge (electron / hole) injection / transport materials based on chiral long-chain molecules have been produced successively, realizing circularly polarized luminescent spin-LEDs with excellent optoelectronic properties. Although spin-LED devices of this structural type combine the spin selectivity caused by chiral materials and the excellent optoelectronic properties of luminescent materials, their low chiral-induced spin selectivity (CISS) efficiency limits the spin injection efficiency and spin-polarized light emission intensity of the device.

[0003] In order to optimize the CISS effect of the device, the field-driven driving characteristics of the non-injection AC electroluminescent device (NI-ACEL) are utilized. Under the action of a high-voltage electric field, charges are generated at the interface between the dielectric layer (insulating layer) and the spin-polarized layer instead of being directly injected by external charges. The external electric and magnetic fields generated at the same time can not only provide driving force for the recombination of the active layer excitons, but also optimize the injection efficiency of the spin charges. Therefore, spin-polarized AC electroluminescence (spin-ACEL) obtained based on chiral materials is a good choice for generating efficient spin-polarized light. However, at present, a device can generally only emit polarized light in a single spin direction (left-handed / right-handed), and cannot simultaneously control and generate different spin-polarized lights. The spin polarization rate of spin-LEDs in the prior art is relatively low, which greatly compresses the application scenarios of spin-polarized light-emitting devices. Summary of the invention

[0004] The purpose of the present invention is to provide a spin-polarized AC electroluminescent device, a light-emitting panel and an application. The light-emitting device can efficiently generate spin-polarized light through the chirality-induced spin selectivity of the spin polarization layer, and can simultaneously control and generate light with different spin polarization directions (left-handed / right-handed) in the same plane, and change the luminous intensity by adjusting the driving voltage or frequency, thereby breaking through the limitation that the current spin-LED can only generate single spin-polarized light.

[0005] The present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a spin-polarized alternating current electroluminescent device, which comprises, from bottom to top, a substrate (1), an electrode layer (2) below, a dielectric layer (3) below, a hole injection layer (4), a hole transport layer (5), a light-emitting layer (6), an electron transport layer (7), an electron injection layer (8), an upper dielectric layer (3), an upper electrode layer (2) and a protective layer (9); a single spin polarization layer (11) is used to simultaneously control and generate light with different spin polarization directions in the same plane, and to change the luminous intensity by adjusting the driving voltage or frequency; the spin polarization layer (11) is located between the hole transport layer (5) and the light-emitting layer (6) or between the light-emitting layer (6) and the electron transport layer (7); and the material used to make the spin polarization layer (11) is selected from chiral materials.

[0007] According to some embodiments, the chiral material is selected from organic chiral molecular materials, perovskite chiral materials or MOF chiral materials.

[0008] In a second aspect, the present invention provides a spin-polarized AC electroluminescent device with a coplanar electrode structure, which comprises, from bottom to top, a substrate (1), two coplanar electrode layers (2), a dielectric layer (3), a hole injection layer (4), a hole transport layer (5), two coplanar spin polarization layers (11), two coplanar light-emitting layers (6), an electron transport layer (7), an electron injection layer (8), a sensing layer (10) and a protective layer (9), wherein the two spin polarization layers (11) are used for selective injection and composite light emission of left and right spin polarized light, and the material for making the spin polarization layers (11) is selected from chiral materials; wherein the upper and lower order of the two coplanar spin polarization layers (11) and the two coplanar light-emitting layers (6) is interchangeable.

[0009] According to some embodiments, the two co-planar spin polarization layers (11) and the two co-planar light-emitting layers (6) are orthogonal.

[0010] According to some embodiments, the two co-planar spin polarization layers (11) and the two co-planar light emitting layers (6) are parallel.

[0011] In a third aspect, the present invention provides a spin-polarized AC electroluminescent panel, which includes a plurality of pixel units arranged in combination, wherein a single pixel unit includes three spin-polarized AC electroluminescent devices according to the above-mentioned coplanar electrode structure, and are alternately arranged in the order of RGB.

[0012] In a fourth aspect, the present invention provides an application of the above-mentioned spin-polarized AC electroluminescent device, wherein the spin-polarized AC electroluminescent device is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.

[0013] In a fifth aspect, the present invention provides an application of a spin-polarized AC electroluminescent device having the above-mentioned coplanar electrode structure, wherein the spin-polarized AC electroluminescent device is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.

[0014] In a sixth aspect, the present invention provides an application of the above-mentioned spin-polarized AC electroluminescent panel, wherein the spin-polarized AC electroluminescent panel is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a spin-polarized AC electroluminescent device, a light-emitting panel and an application thereof, which realizes a spin-ACEL that generates spin-polarized light through the chirality-induced spin selectivity of a spin polarization layer, i.e., a spin-AC electroluminescent device. The device can efficiently generate spin-polarized light, overcoming the problem of low spin polarization rate of spin-LED in the prior art. The device can simultaneously control and generate light of different spin polarization directions (left-handed / right-handed) in the same plane, and change the luminous intensity by adjusting the driving voltage or frequency, thereby breaking through the limitation that the current spin-LED can only generate single spin polarized light.

[0017] The present invention further provides a self-luminous pixelated spin-polarized AC electroluminescent panel with a three-dimensional display effect, which includes a plurality of pixel units arranged in combination, and a single pixel unit includes three coplanar spin-polarized AC electroluminescent devices, which are arranged alternately in the order of RGB. Under the drive of a specific AC voltage and frequency, the light-emitting position, display period and light-emitting color of left-handed or right-handed polarized light are controlled respectively. The display content of the left and right eyes is screened respectively by a polarizer, so that the left and right eyes receive spin-polarized light in different directions, thereby generating a parallax effect, and finally realizing a three-dimensional display.

[0018] In specific applications, the present invention solves the problems of high power consumption, high cost, heavy weight and difficulty in sharing display content in existing independent binocular self-luminous three-dimensional display systems (such as virtual reality (VR), augmented reality (AR), and mixed reality (MR) head-mounted display devices); the present invention also overcomes the problems of large light intensity loss, difficulty in mass production, and strict glasses wearing angle in polarized light projection reflection three-dimensional display systems (such as movie theaters and large three-dimensional projection halls). The left-right circularly polarized light generated by chiral materials through chirality-induced spin selection is different from the traditional mutually perpendicular polarized light. After wearing specific polarized glasses, a more stable three-dimensional display can be obtained without angle restrictions, and there will be no parallax blur caused by tilting the head. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the three-dimensional display effect of a spin-polarized alternating current electroluminescent device provided in an embodiment of the present invention.

[0020] Figure 2 This is the light-emitting principle of the coplanar structure ACEL device provided by the embodiment of the present invention.

[0021] Figure 3 A structural diagram of a spin-polarized AC electroluminescent device provided in an embodiment of the present invention.

[0022] Figure 4 A structural diagram of a spin-polarized AC electroluminescent device with a coplanar electrode structure provided in an embodiment of the present invention.

[0023] Figure 5 A three-dimensional schematic diagram of a spin-polarized AC electroluminescent device with a coplanar electrode structure provided by an embodiment of the present invention.

[0024] Figure 6 This is a rendering of Example 1 provided for an embodiment of the present invention.

[0025] Figure 7 This is a rendering of Example 2 provided for an embodiment of the present invention.

[0026] Figure 8 This is a rendering of Example 3 provided in accordance with an embodiment of the present invention.

[0027] Fig. 9 This is a rendering of Example 4 provided in accordance with an embodiment of the present invention.

[0028] In the figure:

[0029] Substrate 1; electrode layer 2; dielectric layer 3; hole injection layer 4; hole transport layer 5; light emitting layer 6; electron transport layer 7; electron injection layer 8; protective layer 9; induction layer 10; spin polarization layer 11. DETAILED DESCRIPTION

[0030] The technical principles of the present invention are as follows:

[0031] The present invention is based on the non-injected AC electroluminescent device and introduces a chiral material as a spin polarization layer, so that the device generates spin polarized light under AC drive. Furthermore, since the current mainstream device is DC-driven electroluminescent, some teams have already combined a spin polarization layer on the basis of DC-driven electroluminescent devices as a polarized light display. However, this type of device firstly does not have good spin polarization characteristics, while the driving mechanism of the AC electroluminescent device used in the present invention is a high-voltage electric field (between tens of volts and hundreds of volts. For devices based on quantum dots, two-dimensional materials (such as MoS2) or nanowires, the driving voltage may be between tens of volts and hundreds of volts, depending on the band gap of the material and the device structure. Inorganic ACEL devices generally require a higher voltage (100V to 1000V or more), and the typical driving frequency is in the range of hundreds of Hz to several kHz), which is beneficial to improve the spin polarization rate of the chiral spin polarization layer; secondly, the coplanar structure adopted by the light-emitting device of the present invention not only enables it to obtain the function of displaying different effects at the same time (displaying different colors and different left-handed and right-handed types of light on the left and right), but also uses only one driving unit to obtain two different display areas, which is equivalent to two sandwich structure devices. The above comparisons are all based on the traditional sandwich structure. When the device wants to realize left-handed and right-handed polarized light respectively, it needs to be prepared into two devices separately. Therefore, the coplanar structure device can use a device under drive to realize the simultaneous display of two spin-polarized lights, thereby reducing power consumption, saving materials and preparation costs, and simplifying the preparation steps.

[0032] The present invention is described in detail below in conjunction with the embodiments and the accompanying drawings, but it should be understood that the embodiments and the accompanying drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations included in the scope of the invention spirit of the present invention fall within the protection scope of the present invention. The present invention is further described below in conjunction with the accompanying drawings.

[0033] The present invention provides three spin-polarized AC electroluminescent devices, which are as follows:

[0034] Example 1

[0035] This embodiment provides a spin-polarized AC electroluminescent device, which has the following structure:

[0036] like Figure 3, from bottom to top, it includes a substrate 1, an electrode layer 2 below, a dielectric layer 3 below, a hole injection layer 4, a hole transport layer 5, a spin polarization layer 11, a light emitting layer 6, an electron transport layer 7, an electron injection layer 8, an upper dielectric layer 3, an upper electrode layer 2 and a protective layer 9. The spin polarization layer 11 may be located between the hole transport layer 5 and the light emitting layer 6 (e.g. Figure 3 .a) or between the light-emitting layer 6 and the electron transport layer 7 (such as Figure 3 .b). The material for making the spin polarization layer 11 is selected from chiral materials, such as organic chiral molecular materials, perovskite chiral materials or MOF chiral materials. The spin polarization layer 11 is used to simultaneously control and generate light with different spin polarization directions in the same plane, and the luminous intensity is changed by adjusting the driving voltage or frequency, thereby breaking through the limitation that the current spin-LED can only generate single spin polarization light.

[0037] This embodiment is based on a non-injection AC electroluminescent device and introduces a chiral material as a spin polarization layer, so that the device generates spin polarized light under AC driving.

[0038] like Figure 6 The top view on the left shows the schematic diagram of the combination of component 6 and component 11. The filled color corresponds to the luminous color of component 6; the "rotation direction arrow" corresponds to the spin polarization direction (right-handed) of component 11. The "spiral arrow" on the right side of the structure diagram indicates the spin direction (right-handed) of the generated spin polarized light; the "white arrow" indicates its luminous direction (downward). (Right-handed and left-handed can be replaced)

[0039] Example 2

[0040] This embodiment provides a spin-polarized AC electroluminescent device with a coplanar electrode structure, which has the following structure:

[0041] like Figures 4-5 , from bottom to top, it includes a substrate 1, two coplanar electrode layers 2, a dielectric layer 3, a hole injection layer 4, a hole transport layer 5, two coplanar spin polarization layers 11, two coplanar light-emitting layers 6, an electron transport layer 7, an electron injection layer 8, a sensing layer 10 and a protective layer 9. The spin polarization layer 11 can be located between the hole transport layer 5 and the light-emitting layer 6 (e.g. Figure 4 .a) or between the light-emitting layer 6 and the electron transport layer 7 (such as Figure 4 .b), and the electrode layer 2, the light-emitting layer 6 and the spin polarization layer 11 are all composed of two coplanar pieces. Based on the charge induction mechanism, the charge distribution on the surface of the sensing layer 10 changes under the action of the AC electric field and generates charges opposite to those of the electrode. These changes will affect the charge distribution in the transmission material in contact with the sensing layer, thereby promoting the injection of electrons or holes.

[0042] The device is based on the coplanar electrode structure NI-ACEL (such as Figure 2 ), using the spin selectivity of chiral materials, the selective injection and composite luminescence of left-handed and right-handed spin-polarized light are realized. The left and right eyes receive the corresponding spin-polarized light through polarizers, thus realizing a three-dimensional display effect ( Figure 1 ). This technology can be applied to the production of new three-dimensional display panels.

[0043] By taking advantage of the coplanar electrode structure, not only is it possible to obtain the function of simultaneously displaying different effects (displaying different colors and different left-right rotating types of light on the left and right), but also two different display areas can be obtained with only one driving unit, which is equivalent to the light-emitting devices provided in two Embodiments 1.

[0044] like Figure 7 , the top view on the left is a schematic diagram of the combination of components 6, 6' and components 11, 11'. Among them, the two filling colors correspond to the two luminous colors of components 6 and 6' respectively; the two "rotation direction arrows" correspond to the spin polarization directions (right-handed and left-handed) of components 11 and 11' respectively. The two "spiral arrows" in the right structural diagram respectively represent the spin directions (right-handed and left-handed) of the generated spin-polarized light; the "white arrow" and the "black arrow" both indicate its luminous direction (downward). The right-handed and left-handed positions can be replaced.

[0045] Example 3

[0046] This embodiment provides an orthogonal spin polarization AC electroluminescent device, which has the following structure:

[0047] like Figure 8 , its structure is consistent with the structure and preparation order of the light-emitting device provided in Example 2, but the dual-region spin polarization layer and the dual-region light-emitting layer are orthogonal, that is, they are arranged in a 90-degree cross. The beneficial effect of the orthogonal structure is that the display area can be expanded into four, and each area can be matched with the corresponding display color and polarization direction. Compared with implementation 2, it has a higher subdivision effect and is suitable for complex application scenarios; the top view on the left side of the figure shows a schematic diagram of the combination of components 6, 6' and components 11, 11'. Among them, the two filling colors correspond to the two luminous colors of components 6 and 6' respectively; the two "rotation direction arrows" correspond to the spin polarization directions (right-handed and left-handed) of components 11 and 11' respectively. The two "spiral arrows" in the structural diagram on the right respectively indicate the spin directions (right-handed and left-handed) of the generated spin-polarized light; the "white arrow" and the "black arrow" both indicate its light-emitting direction (downward). (Where the right-handed and left-handed positions can be replaced)

[0048] Example 4

[0049] like Fig. 9The present embodiment provides a pixelated spin-polarized alternating current light-emitting panel, which includes a plurality of spliced ​​pixel units, a single pixel unit includes the three coplanar light-emitting devices of red, green and blue in Example 2, and the single light-emitting device includes from bottom to top a substrate 1, two pixelated coplanar electrode layers 2, a dielectric layer 3, a hole injection layer 4, a hole transport layer 5, a pixelated coplanar spin polarization layer 11, a pixelated coplanar light-emitting layer 6, an electron transport injection layer 7, a sensing layer 10 and a protective layer 9, and are arranged alternately in the order of RGB.

[0050] Specifically, the three independent coplanar structure devices of Embodiment 2 are: (R) red left-handed-red right-handed, (G) green left-handed-green right-handed, and (B) blue left-handed-blue right-handed. Fig. 9 A pixelated pixel unit constituting a white left-right rotating unit, and a plurality of pixel units are arranged alternately to constitute a display panel, that is, a pixelated spin-polarized alternating current luminous panel.

[0051] This embodiment is based on the structure of the light emitting device provided in Embodiment 2. This embodiment uses red, green and blue (RGB) three colors to be arranged alternately to form a pixel unit that can independently control the color and left-right rotation direction.

[0052] Description of this embodiment:

[0053] (1) The light emitted by the display panels currently on the market is not spin-selective, that is, it is visible to the ordinary human eye, and even wearing polarized lenses cannot detect the difference. Therefore, the display panel produced by this embodiment can selectively produce left-handed and right-handed light of different colors. In the normal observation mode, the human eye can display images normally. When wearing specific polarized lenses, the left eye only receives left-handed light, and the right eye only receives right-handed light, so that the left and right eye images are different, resulting in parallax, and finally the brain forms a three-dimensional image.

[0054] (2) This embodiment is prepared based on a coplanar structure. The biggest advantage of the traditional sandwich structure is that it can drive and obtain twice the display pixels using the same number of drivers as the traditional structure. It has the advantages of low power consumption and low cost, and is the basis of a small 3D imaging system with a cinema-level experience.

[0055] (3) The pixelated device provided in this embodiment emphasizes the left-right rotating light of the same color under a set of driving, that is, the function (color and left-right rotating light type) of each area is specified.

[0056] Example 5

[0057] This embodiment provides a method for preparing a spin-polarized AC electroluminescent device, and the preparation methods of each layer are as follows:

[0058] S1: substrate cleaning:

[0059] A conductive glass substrate on which an indium tin oxide (ITO) electrode pattern has been deposited and etched (single-electrode ITO is used for the spin-polarized AC electroluminescent device; the electrodes of the coplanar electrode structure spin-polarized AC electroluminescent device and the orthogonal spin-polarized AC electroluminescent device use ITO with coplanar electrodes) is ultrasonically cleaned for 15 to 30 minutes with deionized water, ethanol (95% (v / v)) and isopropanol (99% (v / v)), respectively, and then its surface is subjected to ultraviolet irradiation treatment for 15 to 30 minutes with an ultraviolet ozone cleaning machine to improve the surface energy of the substrate and facilitate the solution spin coating and spreading;

[0060] S2: Preparation and preparation of dielectric layer materials

[0061] Spin coating type: polyvinylidene fluoride (PVDF) and its copolymers (for example: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE), polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE)), polyimide (PI), polyvinyl alcohol (PVA), etc. The solvent is a polar solvent such as N,N-dimethylformamide (DMF), acetone, N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc) or tetrahydrofuran (THF);

[0062] Evaporation type: metal or non-metal oxides such as aluminum oxide (Al2O3), aluminum nitride (AlN), zirconium dioxide (ZrO2), strontium titanate (SrTiO3), silicon dioxide (SiO2), barium titanate (BaTiO3) or titanium dioxide (TiO2).

[0063] Preparation process of dielectric layer spin coating: the spin coating material and the solvent are mixed at a concentration of 50-150 mg / mL, and fully heated and stirred on a magnetic stirring heating table until completely dissolved (50-80°C; 300-1500 rpm) to obtain a dielectric layer spin coating solution for use, and the above solution is spin coated on a coating machine at a speed of 500-2500 rpm for 10-60 seconds to obtain a uniform dielectric layer film;

[0064] Evaporation preparation process: Place the high-purity particles / target sheets of the evaporation type on the evaporation boat, and coat them through the thermal evaporation coating machine / magnetron sputtering machine, controlling the evaporation rate at The final dielectric layer thickness is 50 to 120 nm.

[0065] S3: Charge injection / transport layer material configuration and preparation

[0066] The charge injection / transport layer is divided into: hole injection / transport layer and electron injection / transport layer.

[0067] Among them, the hole injection / transport layer is generally selected from: poly(3,4-ethylenedioxythiophene)-sodium polystyrene sulfonate complex (PEDOT-PSS), poly(N-vinylcarbazole) (PVK), poly(9,9-dioctylfluorene-2,7-yl-cothiophene) (TFB), poly[di(4-butylphenyl)aminophenyl] (polyTPD), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (NPB) or 2,2',7,7'-tetrakis[phenyl(4-phenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), etc.; the solvent can be selected from: chloroform, tetrahydrofuran, dichlorobenzene, chlorobenzene, dichloromethane, water, isopropanol, N-methyl-2-pyrrolidone or dimethyl sulfoxide, etc. (Wherein, the dispersion concentration of PEDOT:PSS is 0.5 to 3 (w / w))

[0068] Among them, the electron injection / transport layer generally uses: zinc oxide (ZnO), magnesium-doped zinc oxide (ZnMgO), fullerene (C60), copper phthalocyanine (CuPc), fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), lithium fluoride / aluminum (LiF / Al), aluminum trifluoride (AlF3), magnesium fluoride (MgF2), two-dimensional materials composed of transition metal carbides, nitrides or carbonitrides (MXene), etc.; the solvent can be selected from: ethanol, methanol, isopropanol, deionized water, chloroform, chlorobenzene, dichlorobenzene or tetrahydrofuran; for materials such as lithium fluoride / aluminum (LiF / Al), aluminum trifluoride (AlF3) or magnesium fluoride (MgF2), thin films are usually prepared by evaporation or sputtering.

[0069] S31: Spin coating preparation process of electron injection / transport layer: mix / disperse the spin coating material and the solvent at a concentration of 5-25 mg / mL, and fully heat and stir on a magnetic stirring heating table until completely dissolved (50-90°C; 300-1500rpm) to obtain the electron injection / transport layer spin coating solution for use, and spin coat the above solution on a coating machine at a speed of 2000-4000rpm for 30-60s to obtain a uniform electron injection / transport layer film; Evaporation preparation process: place the high-purity particles of the evaporation type on an evaporation boat, and coat them with a thermal evaporation coating machine, controlling the evaporation rate at The final thickness of the electron injection / transport layer is 1 to 10 nm.

[0070] S32: Hole injection / transport layer spin coating preparation process: The spin coating material and the solvent are mixed / dispersed at a concentration of 5-25 mg / mL, and are fully heated and stirred on a magnetic stirring heating table until completely dissolved (50-90°C; 300-1500 rpm) to obtain a hole injection / transport layer spin coating solution for use, and the above solution is spin coated on a coating machine at a speed of 2000-4000 rpm for 30-60s to obtain a uniform hole injection / transport layer film; Evaporation preparation process: The high-purity particles of the evaporation type are placed on an evaporation boat, and the film is coated by a thermal evaporation coating machine, and the evaporation rate is controlled at The final thickness of the hole injection / transport layer is 1 to 10 nm.

[0071] S4: Light-emitting layer material configuration and preparation

[0072] The light-emitting layer is divided into: an organic light-emitting layer, a quantum dot light-emitting layer, a perovskite light-emitting layer or a ZnS powder light-emitting layer.

[0073] S41: Configuration and preparation of organic light-emitting layer:

[0074] Organic luminescent materials: such as aluminum tris(8-hydroxyquinoline) (Alq3) or 1,4-bis(phenyl-1,10-phenanthroline) (Bphen), etc.; solvents: chloroform, dichlorobenzene or chlorobenzene, etc.;

[0075] Dopant: Red, green, and blue dopants can be selected, such as iridium complexes (Ir(ppy)3) for green luminescence and europium complexes (Eu(TTA)3Phen) for red luminescence.

[0076] Configuration and preparation method: First, add the organic light-emitting material and the dopant to chloroform or dichlorobenzene in the required weight ratio, stir until completely dissolved, and form a uniform solution (the concentration of the organic light-emitting material in the solvent is generally 1-5wt%). Next, the spin coating speed is generally 1000-4000rpm, and the time is 30-60s to obtain a uniform organic light-emitting layer. Then, the coated substrate is heated to 80-120°C in a vacuum drying oven for 10-30min to remove the solvent and enhance the density and stability of the film layer. Finally, the thickness of the organic light-emitting layer is 50-200nm.

[0077] S42: Configuration and preparation of quantum dot light-emitting layer:

[0078] Quantum dot materials: semiconductor nanoparticles such as CdSe, CdS, ZnS or PbS;

[0079] Solvent: toluene, methane, octane, chloroform or ethyl acetate, etc.;

[0080] Ligand: octanoic acid, oleylamine or oleic acid, etc.

[0081] Configuration and preparation method: First, mix the quantum dot nanoparticles with a solvent, add an appropriate amount of ligand, and ultrasonically disperse for 10 to 30 minutes in an ultrasonic cleaning process to ensure that the quantum dots are evenly dispersed in the solution (the concentration of the quantum dot dispersion is usually 5 to 20 mg / mL). Next, apply the quantum dot dispersion to a pre-treated substrate. The spin coating speed is generally 1000 to 2000 rpm for 30 to 60 seconds. Then, dry the film at 60 to 100°C for 10 to 20 minutes to remove the solvent, and cure the quantum dot light-emitting layer by moderate heat treatment. Finally, the thickness of the quantum dot light-emitting layer is 20 to 100 nm.

[0082] S43: Configuration and preparation of perovskite light-emitting layer:

[0083] Perovskite precursors: formamidinium lead iodide (FAPbI3), lead bromide (PbBr2), methylammonium lead iodide (MAPbI3), etc.; solvents: N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or γ-butyrolactone, etc.; additives: cesium chloride (CsCl) or ammonium hydride, etc.

[0084] Configuration and preparation method: First, dissolve the perovskite precursor in DMF or DMSO, add an appropriate amount of additives to adjust the growth of perovskite crystals, and stir until completely dissolved to obtain a precursor solution (the concentration of the perovskite precursor solution is usually 0.5-1.5M). Next, spin-coat the perovskite precursor solution on a clean substrate at a speed of 2000-4000rpm for 30-60s. Then, place the spin-coated substrate on a hot stage and anneal it at 100-150°C for 10-30min to promote the formation of perovskite crystals and obtain a high-quality perovskite light-emitting layer.

[0085] S44: Configuration and preparation of ZnS powder luminescent layer:

[0086] ZnS powder: doped ZnS powder, such as copper (Cu), manganese (Mn) or chlorine (Cl) doped ZnS powder; binder: transparent resin, acrylic acid, polydimethylsiloxane (PDMS) or polyurethane (TPU) etc.; solvent: isopropyl alcohol or toluene etc.

[0087] Configuration and preparation method: First, mix the ZnS powder with the binder, add an appropriate amount of solvent, and stir until a uniform slurry is formed (the slurry concentration of the ZnS powder luminescent layer is usually 30-70wt%). Next, use screen printing or blade coating to evenly apply the slurry on the substrate. The thickness and uniformity depend on the requirements of the luminescent layer. Then, slowly dry at room temperature or 60-80°C to ensure the integrity and uniformity of the powder luminescent layer. (To improve mechanical strength and durability, curing treatment can be performed at 100-120°C to ensure that the luminescent layer is firmly bonded and has stable performance.)

[0088] S5: Spin polarization layer material configuration and preparation

[0089] The spin polarization layer is divided into: organic chiral molecular materials, perovskite chiral materials or MOF chiral materials.

[0090] S51: Configuration and preparation of organic chiral molecular spin polarization layer:

[0091] Organic chiral molecules: such as chiral biphenyl derivatives (R-BINOL or S-BINOL) or chiral helical polymers, etc.

[0092] Dopant: chiral ligand or metal complex (such as chiral iridium complex or chiral ruthenium complex).

[0093] Solvent: chloroform, tetrahydrofuran (THF) or dichlorobenzene, etc.

[0094] Preparation method: First, dissolve the organic chiral molecule and an appropriate amount of dopant in chloroform or dichlorobenzene, stir until completely dissolved, and form a uniform chiral molecule solution. The concentration of the dopant is usually 1-5wt%. Use spin coating (2000-3000rpm, 30-60s) to evenly spin coat the solution to form a uniform organic chiral film. Then, dry the film at 60-100°C for 10-20min, remove the solvent and solidify to form an organic chiral molecule spin polarization layer (usually 50-150nm thick) with good spin polarization carrier injection performance.

[0095] S52: Configuration and preparation of chiral spin polarization layers in perovskite:

[0096] Perovskite precursors: formamidinium lead iodide (FAPbI3) or lead bromide (PbBr2), etc.

[0097] Chiral additives: chiral amines (such as R- or S-phenylethylamine) or chiral acids (such as R- or S-lactic acid), etc.

[0098] Solvent: N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), etc.

[0099] Preparation method: First, dissolve the perovskite precursor in DMF or DMSO, then add the chiral additive and stir until completely dissolved to form a uniform chiral perovskite precursor solution. The concentration of the chiral additive is usually 0.1-10 mol% to adjust the chirality of the perovskite crystal. Then, the chiral perovskite precursor solution is spin-coated on a pre-treated substrate at a spin coating condition of 2000-4000 rpm for 30-60 seconds. A uniform chiral perovskite film is formed after spin coating. Finally, the spin-coated substrate is placed on a hot stage and annealed at 100-150°C for 10-30 minutes to promote the growth of the perovskite crystal and the formation of the chiral structure, thereby obtaining a perovskite chiral spin polarization layer (usually 100-300 nm thick) with spin-polarized carrier injection capability.

[0100] S53: Configuration and preparation of MOF chiral spin polarization layer:

[0101] Chiral nanoparticles: such as chiral gold nanoparticles or chiral silica nanoparticles.

[0102] Chiral metal-organic frameworks (MOFs): such as chiral lanthanide metal-organic frameworks.

[0103] Solvent: ethanol, water or isopropanol, etc.

[0104] Chiral nanoparticles or MOFs solution preparation:

[0105] Preparation method: First, disperse the chiral nanoparticles or MOFs in ethanol or water, and form a uniform dispersion by ultrasound or stirring. The concentration of the chiral material can be adjusted according to the application requirements, usually in the range of 0.1 to 5wt%. Then, the chiral nanoparticles or MOFs dispersion is evenly spin-coated on the substrate by spin coating to form a chiral material film. Finally, the solvent can be removed by solvent volatilization or drying (usually annealing at 100 to 150°C for 10 to 30 minutes) to obtain a MOF chiral spin polarization layer with spin-polarized carrier injection capability (usually 50 to 200 nm thick).

[0106] S6: Electrode layer / sensing layer material configuration and preparation

[0107] S61: Preparation of silver / aluminum (Ag / Al) common electrode layer by thermal evaporation:

[0108] Material configuration:

[0109] Silver target: high purity silver or aluminum (Ag / Al, purity is usually above 99.99%).

[0110] Preparation method:

[0111] Preparation of the evaporation system: First, place the silver or aluminum target (usually in the form of particles or flakes) in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, select and place a mask corresponding to the shape of a common electrode, fix the substrate on the mask substrate table in the evaporation chamber, and ensure that the substrate surface faces the evaporation boat. Then, evaporate the evaporation system to a vacuum of preferably 10-5 to 10-6 Torr. Slowly increase the current of the evaporation boat to gradually heat the target. Silver begins to evaporate at 960°C / aluminum at 660°C. Control the evaporation rate at To ensure the formation of a uniform and dense silver / aluminum film. The thickness of the film is monitored in real time by a quartz crystal monitoring system. Usually the thickness of the silver / aluminum electrode layer is controlled at 50-150nm. Finally, after the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure.

[0112] S62: Preparation of silver / aluminum (Ag / Al) coplanar electrode layer by thermal evaporation:

[0113] Material configuration:

[0114] Silver target: high purity or aluminum (Ag / Al, purity is usually above 99.99%).

[0115] Preparation method:

[0116] Preparation of the evaporation system: First, place the silver or aluminum target (usually in the form of particles or flakes) in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, select and place a mask with a coplanar electrode shape, and fix the substrate upside down on the mask substrate table in the evaporation chamber, making sure that the substrate surface faces the evaporation boat. Then, evaporation system is evacuated, and the vacuum degree is preferably 10 -5 ~10 - 6 Torr. Slowly increase the current of the evaporation boat and gradually heat the target. Silver starts to evaporate at 960℃ / aluminum at 660℃. Control the evaporation rate at To ensure the formation of a uniform and dense silver / aluminum film. The thickness of the film is monitored in real time by a quartz crystal monitoring system. Usually the thickness of the silver / aluminum electrode layer is controlled at 50-150nm. Finally, after the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure.

[0117] S63: The sensing layer is applied to the coplanar electrode structure, that is, it is only applied to Embodiment 2, Embodiment 3 and Embodiment 4. The principle is as follows Figure 2As shown. In the ACEL device with a coplanar electrode structure, the formation of the induction / polarity layer and the generation mechanism of the electric field are mainly achieved through the redistribution of charges and the polarization effect of polar molecules under the action of AC voltage. When AC voltage is applied to the coplanar electrodes, a transverse electric field is formed between these electrodes, inducing the orientation polarization of the polar molecules in the light-emitting layer or the dielectric layer, or generating an induced dipole moment in the non-polar molecules, thereby forming a polarity layer. The alternating change of the electric field causes the charges to move and accumulate periodically in the polarity layer, further enhancing the intensity of the electric field. The electric field drives the material in the light-emitting layer to emit light through the mechanism of electron excitation and photon release. In essence, the induction layer is consistent with the electrode layer material, but the evaporation process requires the replacement of the mask so that the layer can cover the electrodes connected to each layer in order to form an electric bridge.

[0118] S7: Packaging:

[0119] In order to prevent the device from oxidation and water vapor corrosion, the device is packaged after all preparations are completed. Glass or heat-curing / UV-curing polymer materials can be used as a protective layer for sealing.

[0120] The following are the preparation process descriptions of Examples 1 to 3 respectively:

[0121] 1. Example 1 Preparation of spin-polarized AC electroluminescent device:

[0122] The spin-polarized AC electroluminescent device is a traditional sandwich structure. Figure 3 As shown, it is substrate / electrode layer / dielectric layer / hole injection layer / hole transport layer / spin polarization layer / luminescent layer / electron transport layer / electron injection layer / dielectric layer / electrode layer / protective layer, so the preparation steps are S1-S61-S2-S32-S5-S4-S31-S2-S61-S7. The preparation process of each layer structure meets the preparation conditions and parameters of each layer.

[0123] The spin polarization layer may be located between the hole transport layer and the light emitting layer (e.g. Figure 3 .a) or between the light-emitting layer and the electron transport layer (such as Figure 3 .b). At the same time, one or more of the hole injection layer / hole transport layer / electron transport layer / electron injection layer can be appropriately removed according to different requirements. The spin polarization layer can replace any charge injection / transport layer.

[0124] 2. Example 2 Preparation of spin-polarized AC electroluminescent device with coplanar electrode structure:

[0125] The structure and schematic diagram of the coplanar electrode structure spin-polarized AC electroluminescent device are shown in Figure 4 and Figure 5As shown, the structure is substrate / coplanar electrode layer / dielectric layer / hole injection layer / hole transport layer / coplanar spin polarization layer / coplanar light-emitting layer / electron transport layer / electron injection layer / sensing layer / protective layer. Compared with Example 1, Example 2 is that (1) the electrode layer is changed to a coplanar electrode layer; (2) one dielectric layer is omitted; (3) the penultimate layer is replaced by a sensing layer instead of an electrode layer (the two have the same composition but different functions). Therefore, the preparation steps are as follows:

[0126] S1-S62-S2-S32-S5-S4-S31-S63-S7, the preparation process of each layer meets the preparation conditions and parameters of each layer.

[0127] The spin polarization layer may be located between the hole transport layer and the light emitting layer (e.g. Figure 4 .a) or between the light-emitting layer and the electron transport layer (such as Figure 4 .b). At the same time, one or more of the hole injection layer / hole transport layer / electron transport layer / electron injection layer can be appropriately removed according to different needs. The spin polarization layer can replace any charge injection / transport layer. In addition Figure 4 In the figure, 6 and 6' indicate that light-emitting materials of different colors or types can be used; 11 and 11' indicate that chiral spin materials of different spin directions can be used.

[0128] In the process of manufacturing the spin-polarized AC electroluminescent device with a coplanar electrode structure, in order to accurately define the coating range of each area in the 6 / 6' layer (light-emitting layer) and the 11 / 11' layer (spin-polarized layer) and prepare for subsequent pixel production, the preparation of the light-emitting layer in S4 and the preparation of the spin-polarized layer in S5 are replaced by S8: photolithography mask. Embodiments 2, 3, and 4 can all adopt step S8, and the specific steps are as follows:

[0129] S81: Photoresist coating and exposure: First, a layer of photoresist is evenly coated on the prepared substrate surface, and the coated photoresist layer is pre-baked through a soft baking process to remove the solvent and make the photoresist layer evenly distributed.

[0130] S82: Mask alignment and exposure: Use a precision lithography machine (such as a stepper or projection lithography machine) to precisely align the prefabricated mask with the photoresist layer on the substrate. The mask is designed according to the graphic and size requirements of each functional layer (such as 6 and 6', 11 and 11') to ensure the precise position and size of each area. During the exposure process, the lithography machine uses ultraviolet light or deep ultraviolet light to irradiate the mask, causing a chemical reaction in the photoresist in the exposure area.

[0131] S83: Development and cleaning: After exposure, the substrate is placed in a developer for development, and the photoresist in the unexposed part is dissolved and washed away to form a photoresist mask of the desired pattern. Then, the developed substrate is cleaned to remove the residual developer and photoresist debris.

[0132] S84: Deposition of material layer (S4 preparation of light-emitting layer and S5 spin polarization layer): Under the protection of the photolithography mask, the required material layer (S4 preparation of light-emitting layer and S5 spin polarization layer) is deposited in the exposed area by spin coating, sputtering, evaporation or chemical vapor deposition (CVD). For example, when forming a hole chiral spin injection layer, the material is deposited only in the area not covered by the mask. After the material deposition is completed, appropriate annealing or curing treatment is performed to ensure the quality and stability of the material layer.

[0133] S85: Stripping photoresist: After the material layer is deposited and necessary heat treatment is performed, the photoresist mask is removed using an organic solvent or plasma etching technology to expose the processed area and complete the patterning of an area.

[0134] S86: Repeat the photolithography step: Repeat the above photolithography and material deposition process. The design of the mask pattern and the adjustment of the exposure step can realize the coating manufacturing of different areas (such as 6' area or 11' area). After each photolithography operation, the photolithography mask is adjusted and produced for the area of ​​the next process layer according to the design requirements.

[0135] Therefore, the steps of preparing Example 2 using the photolithography mask preparation steps are as follows: S1-S62-S2-S32-S5(S8)-S4(S8)-S31-S63-S7

[0136] 3. Example 3 Preparation of orthogonal spin polarized AC electroluminescent device:

[0137] The structure of the orthogonal spin-polarized AC electroluminescent device is substrate / coplanar electrode layer / dielectric layer / hole injection layer / hole transport layer / spin polarized layer / luminescent layer / electron transport layer / electron injection layer / sensing layer / protective layer. That is, the preparation steps are: S1-S62-S2-S32-S5-S4-S31-S63-S7, and the preparation process of each layer meets the preparation conditions and parameters of each layer. Among them, in the process of preparing the luminescent layer 6 and the spin polarized layer 11 of the orthogonal spin-polarized AC electroluminescent device, the areas (6 / 6' and 11 / 11') separated from these two layers are orthogonal (intersecting), while the coplanar electrode structure spin polarized AC electroluminescent device 6 / 6' and 11 / 11' are parallel. Therefore, when preparing layers 6 and 11, it is only necessary to switch the direction of the mask in the corresponding preparation to obtain it.

[0138] Therefore, the steps of preparing Example 3 using the photolithography mask preparation steps are: S1-S62-S2-S32-S5(S8)-S4(S8)-S31-S63-S7.

[0139] The spin polarization layer may be located between the hole transport layer and the light emitting layer (e.g. Figure 4 .a) or between the light-emitting layer and the electron transport layer (such as Figure 4 .b). At the same time, one or more of the hole injection layer / hole transport layer / electron transport layer / electron injection layer can be appropriately removed according to different needs. The spin polarization layer can replace any charge injection / transport layer. In addition Figure 4 In the figure, 6 and 6' indicate that light-emitting materials of different colors or types can be used; 11 and 11' indicate that chiral spin materials of different spin directions can be used.

[0140] During the manufacturing process of orthogonal spin-polarized AC electroluminescent devices, in order to accurately define the coating range of each area in the 6 / 6' layer (light-emitting layer) and the 11 / 11' layer (spin polarization layer) and prepare for subsequent pixel production, photolithography mask technology is also used in the preparation of the S4 light-emitting layer and the S5 spin polarization layer.

[0141] The following are implementation experiments for preparation examples 1 to 3:

[0142] 1. The spin-polarized AC electroluminescent device provided in Example 1 comprises, from bottom to top, a substrate, an electrode layer, a dielectric layer, a hole injection layer / hole transport layer, a spin polarization layer, a light-emitting layer, an electron transport injection layer, a dielectric layer, an electrode layer and a protective layer. The preparation process is as follows:

[0143] The conductive glass substrate on which the indium tin oxide (ITO) electrode pattern (single electrode) had been deposited and etched was ultrasonically cleaned for 20 min with deionized water, ethanol (95% (v / v)) and isopropanol (99% (v / v)), respectively, and then the surface was treated with ultraviolet irradiation in an ultraviolet ozone cleaning machine for 15 min;

[0144] Preparation process of dielectric layer spin coating: polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE) and N,N-dimethylformamide (DMF) were mixed at a concentration of 100 mg / mL, and heated and stirred on a magnetic stirring heating table until completely dissolved (70°C; 1500 rpm) to obtain a dielectric layer spin coating solution for use. The above solution was spin coated on a conductive glass substrate at a speed of 1500 rpm for 40 seconds using a coating machine to obtain a uniform dielectric layer film.

[0145] Preparation process of hole injection layer spin coating: 2 (w / w) poly (3,4-ethylenedioxythiophene) - sodium polystyrene sulfonate complex (PEDOT-PSS) was spin coated on a coating machine at 3000 rpm for 60 seconds to obtain a uniform hole injection layer film.

[0146] Preparation process of hole transport layer spin coating: poly [di (4-butylphenyl) aminophenyl] (polyTPD) and chlorobenzene are mixed at a concentration of 8 mg / mL, and fully heated and stirred on a magnetic stirring heating table until completely dissolved (90 ° C; 1500 rpm) to obtain a hole transport layer spin coating solution for use, and the above solution is spin coated on a coater at a speed of 3000 rpm for 30 seconds to obtain a uniform hole transport layer film.

[0147] Spin coating preparation process of spin polarization layer: dissolve organic chiral biphenyl derivative (R-BINOL) and appropriate amount of chiral iridium complex dopant in chloroform, stir until completely dissolved, and form a uniform chiral molecular solution. The concentration of dopant is usually 2wt%. Use spin coating method (3000rpm, 30s) to evenly spin coat the solution to form a uniform organic chiral film. Then, dry the film at 100℃ for 10min, remove the solvent and solidify to form an organic chiral molecular spin polarization layer with good spin polarization carrier injection performance.

[0148] The process of preparing the quantum dot light-emitting layer by spin coating: CdSe quantum dot nanoparticles were mixed with octane and ultrasonicated for 20 minutes to make the dispersion uniformly dispersed (the concentration of the quantum dot dispersion was 20 mg / mL). Then, the quantum dot dispersion was spin coated on the spin polarization layer. The spin coating speed was 2000 rpm and the time was 30 seconds. Then, the film was dried at 90°C for 10 minutes to remove the solvent.

[0149] Preparation process of electron injection / transport layer spin coating: magnesium-doped zinc oxide (ZnMgO) and ethanol are dispersed at a concentration of 20 mg / mL to obtain an electron injection / transport layer spin coating solution for use, and the above solution is spin coated on the light-emitting layer at a speed of 3000 rpm for 40 seconds to obtain a uniform electron injection / transport layer film.

[0150] The dielectric layer spin coating preparation process: a solution of polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE) and N,N-dimethylformamide (DMF) mixed at a concentration of 100 mg / mL was spin coated on the electron injection / transport layer at a speed of 1500 rpm for 40 seconds using a spin coater to obtain a uniform dielectric layer film.

[0151] Electrode layer evaporation preparation process: Place the silver target in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, fix the substrate on the substrate table in the evaporation chamber, making sure that the substrate surface faces the evaporation boat. Then, evaporation system is evacuated to a vacuum degree of 10-5 Torr. Slowly increase the current of the evaporation boat to gradually heat the silver target. Control the evaporation rate at The thickness of silver is controlled at 100nm. After the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure. Finally, a UV-curable polymer material is used for packaging. A spin-polarized AC electroluminescent device is obtained, such as Figure 6 .

[0152] 2. The coplanar electrode structure spin-polarized AC electroluminescent device of Example 2 comprises, from bottom to top, a substrate, a coplanar electrode layer, a dielectric layer, a hole injection layer, a hole transport layer, a dual-region spin polarization layer, a dual-region light-emitting layer, an electron transport injection layer, a sensing layer and a protective layer. The preparation process is as follows:

[0153] The conductive glass substrate on which the coplanar indium tin oxide (ITO) electrode pattern had been deposited and etched was ultrasonically cleaned for 20 min with deionized water, ethanol (95% (v / v)) and isopropanol (99% (v / v)), respectively, and then the surface was treated with ultraviolet irradiation for 15 min with an ultraviolet ozone cleaner;

[0154] Preparation process of dielectric layer spin coating: polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE) and N,N-dimethylformamide (DMF) were mixed at a concentration of 100 mg / mL, and heated and stirred on a magnetic stirring heating table until completely dissolved (70°C; 1500 rpm) to obtain a dielectric layer spin coating solution for use, and the above solution was spin coated on a conductive glass substrate at a speed of 1500 rpm for 40 seconds using a coating machine to obtain a uniform dielectric layer film;

[0155] Preparation process of hole injection layer by spin coating: 2 (w / w) poly (3,4-ethylenedioxythiophene) - sodium polystyrene sulfonate complex (PEDOT-PSS) was spin coated on a spin coater at a speed of 3000 rpm for 60 s to obtain a uniform hole injection layer film;

[0156] Preparation process of hole transport layer spin coating: poly [di (4-butylphenyl) aminophenyl] (polyTPD) and chlorobenzene are mixed at a concentration of 8 mg / mL, and fully heated and stirred on a magnetic stirring heating table until completely dissolved (90 ° C; 1500 rpm) to obtain a hole transport layer spin coating solution for use, and the above solution is spin coated on a coater at a speed of 3000 rpm for 30 seconds to obtain a uniform hole transport layer film.

[0157] Spin coating process of dual-region spin polarization layer:

[0158] (1) Preparation and coating of R chiral molecule solution: First, an organic chiral biphenyl derivative (R-BINOL) and an appropriate amount of chiral iridium complex dopant are dissolved in chloroform and stirred until completely dissolved to form a uniform R chiral molecule solution. The concentration of the dopant is usually 2wt%. In order to form an R chiral molecule spin polarization layer in a specific area, a layer of photoresist is first evenly coated on the substrate and soft-baked (such as baking at 90°C for 1 minute). Use a photolithography machine to accurately align the designed mask with the substrate and perform ultraviolet light exposure to cause the photoresist in the exposed area to undergo a chemical reaction and harden. After exposure, the substrate is placed in a developer for development treatment to remove the unexposed photoresist and expose half of the substrate surface. In this exposed area, the R chiral molecule solution is evenly coated using a spin coating method (3000rpm, 30 seconds) to form an organic chiral film. Subsequently, the substrate is dried at 100°C for 10 minutes to form an organic chiral molecule spin polarization layer with good R spin polarization carrier injection performance.

[0159] (2) Preparation and coating of S chiral molecule solution: Then, the organic chiral biphenyl derivative (S-BINOL) and an appropriate amount of chiral iridium complex dopant are dissolved in chloroform and stirred until completely dissolved to form a uniform S chiral molecule solution. For the preparation of the S chiral molecule spin polarization layer in the other half area, the photoresist coating and exposure steps are performed again. The mask position is adjusted to cover the area coated with the R chiral molecule solution, exposing the other half area, and a second ultraviolet light exposure and development are performed to remove the exposed photoresist. In the newly exposed area, the S chiral molecule solution is evenly coated using a spin coating method (3000 rpm, 30 seconds). Then, the substrate is dried at 100°C for 10 minutes to form an organic chiral molecule spin polarization layer with different spin directions having good dual spin polarization carrier injection performance.

[0160] Spin coating preparation process of dual-region quantum dot light-emitting layer:

[0161] (1) Preparation and coating of the first color quantum dot dispersion: CdSe quantum dot nanoparticles of one color were mixed with octane and ultrasonically treated for 20 minutes to uniformly disperse the quantum dots (concentration 20 mg / mL). Before forming the quantum dot light-emitting layer on the dual-region spin polarization layer, the substrate was first coated with photoresist and soft-baked. Use a photolithography machine to accurately align the designed mask with the substrate, cover half of the spin polarization layer, and expose to ultraviolet light. After exposure, development is performed to remove the exposed photoresist and expose the other half. Spin coating (2000 rpm, 30 seconds) of the first color quantum dot dispersion was uniformly applied to the exposed area. Afterwards, the substrate was dried at 90°C for 10 minutes to form a part of the quantum dot light-emitting layer.

[0162] (2) Preparation and coating of the second color quantum dot dispersion: Mix the CdSe quantum dot nanoparticles of another color with octane and perform ultrasonic treatment for 20 minutes to ensure uniform dispersion (concentration 20 mg / mL). For the preparation of the quantum dot light-emitting layer in the other half of the area, re-apply the photoresist and expose it. Adjust the mask to cover the coated quantum dot area, expose the remaining spin polarization layer area, and perform ultraviolet light exposure and development steps. Use spin coating (2000 rpm, 30 seconds) to evenly coat the second color of quantum dot dispersion on the newly exposed area. After spin coating, dry the substrate at 90°C for 10 minutes to form a quantum dot light-emitting layer in the dual-color display area.

[0163] Electron injection / transport layer spin coating preparation process: zinc oxide (ZnO) and ethanol are dispersed at a concentration of 20 mg / mL to obtain an electron injection / transport layer spin coating solution for use, and the above solution is spin coated on the light-emitting layer at a speed of 3000 rpm for 40 seconds to obtain a uniform electron injection / transport layer film.

[0164] Preparation process of induction layer evaporation: Place the silver target in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, fix the substrate on the substrate table in the evaporation chamber, make sure the substrate surface faces the evaporation boat, and switch to another mask. Then, evaporation system is evacuated to a vacuum degree of 10 -5 Torr. Slowly increase the current of the evaporation boat to gradually heat the silver target. Control the evaporation rate at The thickness of silver is controlled at 100nm. After the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure. Finally, a UV-curable polymer material is used for packaging. A coplanar electrode structure spin-polarized AC electroluminescent device ( Figure 7 ).

[0165] 3. The coplanar electrode structure orthogonal spin polarization AC electroluminescent device of Example 3 comprises, from bottom to top, a substrate, a coplanar electrode, a dielectric layer, a hole injection layer, a hole transport layer, a dual-region spin polarization layer, an orthogonal region light-emitting layer, an electron transport injection layer, a sensing layer and a protective layer. The preparation process is as follows:

[0166] The conductive glass substrate on which the coplanar indium tin oxide (ITO) electrode pattern had been deposited and etched was ultrasonically cleaned for 20 min with deionized water, ethanol (95% (v / v)) and isopropanol (99% (v / v)), respectively, and then the surface was treated with ultraviolet irradiation for 15 min with an ultraviolet ozone cleaner;

[0167] Preparation process of dielectric layer spin coating: polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE) and N,N-dimethylformamide (DMF) were mixed at a concentration of 100 mg / mL, and heated and stirred on a magnetic stirring heating table until completely dissolved (70°C; 1500 rpm) to obtain a dielectric layer spin coating solution for use. The above solution was spin coated on a conductive glass substrate at a speed of 1500 rpm for 40 seconds using a coating machine to obtain a uniform dielectric layer film.

[0168] Preparation process of hole injection layer by spin coating: 2 (w / w) poly (3,4-ethylenedioxythiophene) - sodium polystyrene sulfonate complex (PEDOT-PSS) was spin coated on a spin coater at a speed of 3000 rpm for 60 s to obtain a uniform hole injection layer film;

[0169] Preparation process of hole transport layer spin coating: poly [di (4-butylphenyl) aminophenyl] (polyTPD) and chlorobenzene are mixed at a concentration of 8 mg / mL, and fully heated and stirred on a magnetic stirring heating table until completely dissolved (90 ° C; 1500 rpm) to obtain a hole transport layer spin coating solution for use, and the above solution is spin coated on a coater at a speed of 3000 rpm for 30 seconds to obtain a uniform hole transport layer film.

[0170] Spin coating process of dual-region spin polarization layer:

[0171] (1) Preparation and coating of R chiral molecule solution: First, an organic chiral biphenyl derivative (R-BINOL) and an appropriate amount of chiral iridium complex dopant are dissolved in chloroform and stirred until completely dissolved to form a uniform R chiral molecule solution. The concentration of the dopant is usually 2wt%. In order to form an R chiral molecule spin polarization layer in a specific area, a layer of photoresist is first evenly coated on the substrate and soft-baked. Then, a pre-designed mask and a photolithography machine (such as a stepper) are used to accurately align the exposure area with the substrate, and ultraviolet light exposure is performed to harden the unexposed area of ​​the photoresist. After exposure, the substrate is placed in a developer for development to remove the exposed photoresist. Next, the R chiral molecule solution is evenly coated on the exposed area using a spin coating method (3000 rpm, 30 seconds) to form half of an organic chiral film. After that, the substrate is dried at 100°C for 10 minutes to form an organic chiral molecule spin polarization layer with good R spin polarization carrier injection performance.

[0172] (2) Preparation and coating of S chiral molecular solution: Next, the organic chiral biphenyl derivative (S-BINOL) and an appropriate amount of chiral iridium complex dopant are dissolved in chloroform and stirred until completely dissolved to form a uniform S chiral molecular solution. For the preparation of the S chiral molecular spin polarization layer in the other half area, the photoresist is coated and exposed again. The mask is readjusted to cover the area coated with the R chiral molecular solution, expose the uncoated area, and expose to ultraviolet light to harden the photoresist in this area. Then, the substrate is placed in a developer for development, the exposed photoresist is removed, and the S chiral molecular solution is evenly coated on the exposed area using a spin coating method (3000 rpm, 30 seconds). After completion, the substrate is dried at 100°C for 10 minutes to form an organic chiral molecular spin polarization layer with different spin directions having good dual spin polarization carrier injection performance.

[0173] Spin coating process of orthogonal region quantum dot light-emitting layer:

[0174] (1) Preparation and coating of the first color quantum dot dispersion: First, CdSe quantum dot nanoparticles of one color were mixed with octane and ultrasonically treated for 20 minutes to ensure that the quantum dots were evenly dispersed (concentration 20 mg / mL). In order to form a quantum dot light-emitting layer in a specific area, a photolithography process was used. First, a layer of photoresist was evenly coated on the formed dual-region spin polarization layer and soft-baked. Then, a pre-designed mask was used to cover half of the area and exposed to ultraviolet light through a photolithography machine. After exposure, a development process was performed to remove the exposed photoresist. The first color of quantum dot dispersion was evenly coated on the exposed area using a spin coating method (2000 rpm, 30 seconds). After that, the substrate was dried at 90°C for 10 minutes to form half of the quantum dot light-emitting layer.

[0175] (2) Preparation and coating of the second color quantum dot dispersion: Then, mix the CdSe quantum dot nanoparticles of another color with octane and perform ultrasonic treatment for 20 minutes to ensure uniform dispersion (concentration 20 mg / mL). For the preparation of the quantum dot light-emitting layer in the other half area, apply photoresist again and perform photolithography exposure. Adjust the mask to cover the coated quantum dot area, expose the remaining area, and perform ultraviolet light exposure and development. Use spin coating (2000 rpm, 30 seconds) to evenly coat the second color of quantum dot dispersion on the exposed area. Finally, dry the substrate at 90°C for 10 minutes to form a quantum dot light-emitting layer with an orthogonal display area.

[0176] Electron injection / transport layer spin coating preparation process: zinc oxide (ZnO) and ethanol are dispersed at a concentration of 20 mg / mL to obtain an electron injection / transport layer spin coating solution for use, and the above solution is spin coated on the light-emitting layer at a speed of 3000 rpm for 40 seconds to obtain a uniform electron injection / transport layer film.

[0177] Preparation process of induction layer evaporation: Place the silver target in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, fix the substrate on the substrate table in the evaporation chamber, make sure the substrate surface faces the evaporation boat, and switch to another mask. Then, evaporation system is evacuated to a vacuum degree of 10 -5 Torr. Slowly increase the current of the evaporation boat to gradually heat the silver target. Control the evaporation rate at The thickness of silver is controlled at 100nm. After the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure. Finally, a UV-curable polymer material is used for encapsulation.

[0178] Orthogonal spin polarized AC electroluminescent device with coplanar electrode structure ( Figure 8 ) By utilizing the orthogonality between the dual-region spin polarization layer and the dual-region light-emitting layer, combined with the design of the ITO conductive glass electrode and any combination of electrodes in pairs, the characteristics of left-handed and right-handed same color display, left-handed and right-handed different color display, same color display with the same spin direction, and different color display with the same spin direction are obtained.

[0179] 4. The pixelated spin-polarized AC electroluminescent panel of Example 4 comprises, from bottom to top, a substrate 1, a pixelated coplanar electrode layer 2, a dielectric layer 3, a hole injection layer 4, a hole transport layer 5, a pixelated coplanar spin polarization layer 11, a pixelated coplanar light-emitting layer 6, an electron transport injection layer 7, a sensing layer 10 and a protective layer 9, and the preparation process is as follows:

[0180] The conductive glass substrate on which the pixelated coplanar indium tin oxide (ITO) electrode pattern had been deposited and etched was ultrasonically cleaned for 20 min with deionized water, ethanol (95% (v / v)) and isopropanol (99% (v / v)), respectively, and then the surface was treated with ultraviolet irradiation in an ultraviolet ozone cleaner for 15 min;

[0181] Preparation process of dielectric layer spin coating: polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene terpolymer (PVDF-TrFE-CFE) and N,N-dimethylformamide (DMF) were mixed at a concentration of 100 mg / mL, and heated and stirred on a magnetic stirring heating table until completely dissolved (70°C; 1500 rpm) to obtain a dielectric layer spin coating solution for use. The above solution was spin coated on a conductive glass substrate at a speed of 1500 rpm for 40 seconds using a coating machine to obtain a uniform dielectric layer film.

[0182] Preparation process of hole injection layer spin coating: 2 (w / w) poly (3,4-ethylenedioxythiophene) - sodium polystyrene sulfonate complex (PEDOT-PSS) was spin coated on a coating machine at 3000 rpm for 60 seconds to obtain a uniform hole injection layer film.

[0183] Preparation process of hole transport layer spin coating: poly [di (4-butylphenyl) aminophenyl] (polyTPD) and chlorobenzene are mixed at a concentration of 8 mg / mL, and fully heated and stirred on a magnetic stirring heating table until completely dissolved (90 ° C; 1500 rpm) to obtain a hole transport layer spin coating solution for use, and the above solution is spin coated on a coater at a speed of 3000 rpm for 30 seconds to obtain a uniform hole transport layer film.

[0184] Pixelated spin polarization layer spin coating preparation process:

[0185] (1) Material preparation: R chiral molecule solution: dissolve an organic chiral biphenyl derivative (R-BINOL) and an appropriate amount of a chiral iridium complex dopant in chloroform, stir until completely dissolved, and form a uniform R chiral molecule solution (the dopant concentration is usually 2 wt%). S chiral molecule solution: dissolve an organic chiral biphenyl derivative (S-BINOL) and an appropriate amount of a chiral iridium complex dopant in chloroform, stir until completely dissolved, and form a uniform S chiral molecule solution (the dopant concentration is usually 2 wt%).

[0186] (2) Pixelated photolithography and spin coating preparation:

[0187] Photoresist coating and pretreatment: a layer of photoresist is evenly coated on the substrate, and soft baking is performed (such as baking at 90°C for 1 minute) to make the photoresist evenly distributed and remove the solvent. Mask template fine alignment and exposure: use a high-precision photolithography machine (such as a stepper photolithography machine) and a precision mask template to accurately align the pattern of each pixel with the substrate. The design of the mask template needs to consider the position and size of each pixel to meet the requirements of high-resolution display. UV exposure is performed to ensure that the photoresist undergoes a chemical reaction and hardens in the pixel area. Development and cleaning: after exposure, the substrate is placed in a developer for development to remove the photoresist in the unexposed area and reveal the exposed substrate of each pixel. Then, the R chiral molecule solution is evenly coated on the exposed pixel area using a spin coating method (3000rpm, 30 seconds). After that, the substrate is dried at 100°C for 10 minutes to form an organic chiral molecule spin polarization layer with good R spin polarization carrier injection performance. Similarly, the S spin polarization layer is deposited on the corresponding part. Among them, the R and S spin polarization layers need to be located on the same pair of coplanar electrode pixels respectively.

[0188] Spin coating preparation process of pixelated quantum dot light-emitting layer:

[0189] (1) Preparation of quantum dot luminescent materials: CdSe quantum dot nanoparticles of three colors (red, green, and blue, RGB) were mixed with octane respectively and subjected to ultrasonic treatment for 20 minutes to uniformly disperse the quantum dots (the concentration of the dispersion was 20 mg / mL).

[0190] (2) Pixelated photolithography and spin coating preparation:

[0191] Photoresist coating and pretreatment: a layer of photoresist is evenly coated on the distributed spin pixel layer, and soft baking is performed (such as baking at 90°C for 1 minute) to make the photoresist evenly distributed and remove the solvent. Mask template fine alignment and exposure: use a high-precision photolithography machine (such as a stepper photolithography machine) and a precision mask template to accurately align the pattern of each pixel with the substrate. The design of the mask template needs to consider the position and size of each pixel to meet the requirements of high-resolution display. UV exposure is performed to ensure that the photoresist chemically reacts and hardens in the pixel area. Development and cleaning: after exposure, the substrate is placed in a developer for development, the photoresist in the unexposed area is removed, and the exposed substrate of each pixel is exposed. Next, the red R quantum dot solution is evenly coated on the exposed pixel area using a spin coating method (3000rpm, 30 seconds). After that, the substrate is dried at 100°C for 10 minutes to form a monochrome-red quantum dot light-emitting layer. Similarly, a monochrome-green quantum dot light-emitting layer and a monochrome-blue quantum dot light-emitting layer are deposited on the corresponding parts. Among them, each single-color quantum dot light-emitting layer needs to be located on two pixel points of the same pair of coplanar electrodes, that is, it needs to just cover the R and S spin polarization layers belonging to the same driving circuit.

[0192] Electron injection / transport layer spin coating preparation process: zinc oxide (ZnO) and ethanol are dispersed at a concentration of 20 mg / mL to obtain an electron injection / transport layer spin coating solution for use, and the above solution is spin coated on the light-emitting layer at a speed of 3000 rpm for 40 seconds to obtain a uniform electron injection / transport layer film.

[0193] Preparation process of induction layer evaporation: Place the silver target in a tungsten wire evaporation boat or a ceramic evaporation boat. Next, fix the substrate on the substrate table in the evaporation chamber, make sure the substrate surface faces the evaporation boat, and switch to another mask. Then, evaporation system is evacuated to a vacuum degree of 10 -5 Torr. Slowly increase the current of the evaporation boat to gradually heat the silver target. Control the evaporation rate at The thickness of silver is controlled at 100nm. After the evaporation is completed, the current is turned off and the system is allowed to cool. After cooling, an inert gas (such as nitrogen) is slowly filled to normal pressure. Finally, a UV-curable polymer material is used for packaging. A pixelated spin-polarized AC electroluminescent device ( Fig. 9 ).

[0194] Circuit design and regulation: Through precise circuit design, every two pixels with different spin directions, quantum dot light-emitting layers with different luminous colors, and corresponding coplanar electrodes and driving circuits are matched to achieve independent electric field control and regulation ( Fig. 9 ). The voltage and current of each pixel are adjusted through external circuits to control the injection and transmission of spin-polarized carriers, thus achieving high-resolution display and fine-tuning of images.

[0195] The following table provides a comparison of Examples 1-4.

[0196]

[0197] Embodiment 1 is based on a sandwich structure, which is also the most traditional structure. Embodiment 1 can achieve the final display effects of Embodiment 2, Embodiment 3 and Embodiment 4, that is, each area is prepared as a sandwich structure device (embodiment 1), but it requires more driving units and complicated preparation structures.

[0198] Embodiment 2 mainly optimizes the structure and utilizes the advantages of the coplanar electrode structure, which not only enables it to obtain the function of simultaneously displaying different effects (displaying different colors and different left-right rotating types of light on the left and right), but also obtains two different display areas with only one driving unit, which is equivalent to two of the above-mentioned sandwich structure devices (embodiment 1); embodiment 4 is essentially obtained based on the device of this coplanar electrode structure, so if the application of embodiment 4 is to be realized, the structure of embodiment 2 must be utilized. The specific difference is that embodiment 2 does not focus on the specific application and the specific function to be realized; while embodiment 4 emphasizes the same color light of left-right rotation under a group of driving, that is, the function of each area (color and left-right rotating light type) is specified.

[0199] The structure and principle of Example 3 are consistent with those of Example 2, except that it can realize richer display functions of customized areas, that is, it can selectively control the color and left-right optical rotation type displayed in a certain area.

[0200] In terms of application, embodiments 1 to 4 can be applied to binocular self-luminous three-dimensional display systems and polarized light projection reflection three-dimensional display systems.

[0201] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A spin-polarized alternating current electroluminescent device, comprising, from bottom to top, a substrate (1), an electrode layer (2) below, a dielectric layer (3) below, a hole injection layer (4), a hole transport layer (5), a light-emitting layer (6), an electron transport layer (7), an electron injection layer (8), an upper dielectric layer (3), an upper electrode layer (2) and a protective layer (9), characterized in that: The spin polarization layer (11) is single and is used for simultaneously controlling and generating light with different spin polarization directions in the same plane, and changing the luminous intensity by adjusting the driving voltage or frequency. The spin polarization layer (11) is located between the hole transport layer (5) and the light-emitting layer (6) or between the light-emitting layer (6) and the electron transport layer (7). The material for making the spin polarization layer (11) is selected from chiral materials.

2. The spin-polarized AC electroluminescent device according to claim 1, characterized in that: The chiral material is selected from organic chiral molecular materials, perovskite chiral materials or MOF chiral materials.

3. A spin-polarized AC electroluminescent device with a coplanar electrode structure, characterized in that: The invention comprises, from bottom to top, a substrate (1), two coplanar electrode layers (2), a dielectric layer (3), a hole injection layer (4), a hole transport layer (5), two coplanar spin polarization layers (11), two coplanar light-emitting layers (6), an electron transport layer (7), an electron injection layer (8), a sensing layer (10) and a protective layer (9); the two spin polarization layers (11) are used for selective injection and composite light emission of left-handed and right-handed spin polarized light; the material for making the spin polarization layers (11) is selected from chiral materials; wherein the upper and lower order of the two coplanar spin polarization layers (11) and the two coplanar light-emitting layers (6) can be interchanged.

4. The spin-polarized AC electroluminescent device with a coplanar electrode structure according to claim 3, characterized in that: The two co-planar spin polarization layers (11) and the two co-planar light-emitting layers (6) are orthogonal to each other.

5. The spin-polarized AC electroluminescent device with a coplanar electrode structure according to claim 3, characterized in that: The two co-planar spin polarization layers (11) are parallel to the two co-planar light-emitting layers (6).

6. A spin-polarized AC electroluminescent panel, characterized in that: It comprises a plurality of pixel units arranged in combination, wherein a single pixel unit comprises three spin-polarized alternating current electroluminescent devices with a coplanar electrode structure according to any one of claims 3 to 5, and the devices are arranged alternately in the order of RGB.

7. An application of a spin-polarized AC electroluminescent device according to any one of claims 1 to 2, characterized in that: The spin-polarized AC electroluminescent device is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.

8. An application of a spin-polarized AC electroluminescent device having a coplanar electrode structure according to any one of claims 3 to 5, characterized in that: The spin-polarized AC electroluminescent device is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.

9. An application of the spin-polarized AC electroluminescent panel according to claim 6, characterized in that: The spin-polarized AC electroluminescent panel is applied to a binocular self-luminous three-dimensional display system and a polarized light projection reflection three-dimensional display system.